Membaca Kearifan Lokal Imah Panggung Bale Atikan Kampung Adat Cireundeu - Purnomo, Agus Dodi; Maarif, Yosi Samsul (Program Studi Desain Interior Unikom, 2019)
Local wisdom of Cireundeu village is the noble values that apply to the community as well as the excellence of the local community. These noble values are also reflected through its cultural products. One of the products of cultural products in the form of architecture is Imah Panggung Bale Atikan. The existence of this building is very important both functionally and symbolically. The functionally building as a place to gather and interact residents, especially children to learn. While symbolically the building has a connotative meaning or message about the teachings of life held by its people. Symbollic messages are conveyed through the architectural form and also the use of materials in the structure of the building. The uniqueness of its architectural form is also the identity of the Cireundeu traditional village. Research methods using the descriptive methods. Architectural and material forms are interesting to study which reflects the local wisdom of Sundanese people especially the Cireundeu community.